(untitled) (Gaceta de Ciencias Veterinarias, 2019)
Environmental enrichment (EE) is a useful paradigm to increase cognition capacity and psychological well-being, as well as an adjuvant in the treatment of neurological disorders and age-related deficits. In this paper we determined the effect of EA on locomotor activity, exploration and habituation using open field test; and about memory and learning valued in the radial maze. Sample consisted of 20 C57BL/6 female mice, divided in 2 equivalent groups: Unenriched Control (CNE) housed in individual cages and Enriched Control (CE) that was housed in group for 2 months in cage that had environmental elements that stimulated exploration, locomotion, cognition and sensory organs. Results shown that mice belonging to EC group displayed a significantly higher horizontal locomotor activity during the first 3 days, with a significantly higher habituation rate, however, vertical displacements (rearing) and habituation of it did not show significantly differences between experimental groups. In the radial maze, EC group incurred in a greater number of errors in the first day (p<0.05), however, learning and memory rates were significantly increased. In conclusion, EE increased locomotor activity, habituation and working memory and should be considered an alternative to improve welfare in healthy or in individuals with cognitive deficits.